Sustainability Status of Data-Limited Fisheries: Global Challenges for Snapper and Grouper - Amorim, Patrícia; Sousa, Pedro; Jardim, Ernesto; Menezes, Gui M. (Frontiers in Marine Science, 2019)
Snapper and grouper are important fisheries resources, with high commercial value and an important role in the livelihoods and food security of many local communities worldwide. However, the status of many snapper and grouper fisheries is unknown, particularly in the small-scale fisheries in developing countries. The main goals of this work are to provide an overview of the current status and trends of these resources and to find alternative sources of information that could be used to inform the status of snapper and grouper fisheries, as well as other data-limited fisheries. Several complementary approaches were explored, including determination of the status of snapper and grouper fisheries based on FAO assessment criteria, analysis of landings time-series trends, and investigation of whether other variables could be used as proxies for their status. About half of these fisheries were classified as overexploited, 30 percent as non-fully exploited and 19 percent as fully exploited. The FAO landings data indicated that the number of overexploited fisheries has been increasing over the years, and that the majority of these fisheries are in transition between fully exploited and overexploited status. The Human Development Index emerged as a potential proxy for the status of the biomass. The multinomial modelling approach explained about 44 percent of the variability observed in the biomass stock status classification data and indicated a high level of correspondence between original and estimated status, which makes this approach very attractive for applying to other data-limited fisheries.